Plantability and influence of the application of graphite associated with the chemical treatment of soybean seeds - Pereira, Julio César [UNESP]; Filho, Aldir Carpes Marques [UNESP]; de Souza, Flávia Luize Pereira [UNESP]; Silva, Paulo Roberto Arbex [UNESP] (My University, 2021)
Brazil stands out among the world's largest soy producers.The uniformity in the deposition of seeds and the correct distribution of plants are important factors for the crop to express its maximum productive potential. The present study aimed to evaluate the influence of the lubricant agent “graphite”, applied during and after the chemical treatment ofsoybean seeds in function ofits longitudinal distribution at different operating speeds.Forthis purpose, a seeder with mechanical type feeder was used, at three working speeds: 4, 6 and 8 km h-1 and conducted in a strip design, organized in a 2x3 factorial scheme, with two different modes of application of graphite and 3 operating speeds. The results presented showed that the addition of graphite concomitantly with the seed treatment,increases the unevenness of sowing, the same occurs in relation to the increase in the speed of operation. Graphite loses lubricating action when added to the seed treatment, increasing the number of failures.
Plantabilidade e influência da aplicação do grafite associado ao tratamento químico de sementes de soja
Keywords: Coefficient of variation; Deficient spacing; Planting speed; Seed distribution; Seed lubricant